TI, TOBACCO INST (Tufts Archival Research Center, 2007)
Document indexing major issues the tobacco industry faces. Includes scientific affairs, public smoking, excise taxes, social costs, advertising restrictions, fire safety and media relations. Gives the background on each issue and the objective of the Tobacco Institute to deal with the issue. Suggests goals and strategies in order to do so.